Development of solid oxide cells via electrode and electrolyte materials engineering - Sun, Yi (Curtin University, 2024)
Solid oxide cells (SOCs) are one of the most promising intermediate conversion devices to solve the intermittency issue of renewable energy and to speed up the energy transition. Developing interface assembly methods for ruling out the side effect of high sintering temperature and discovering new electrolyte materials for reduced operation temperature are keys for expanding the usage of SOCs. This thesis provides an extensive and profound study from electrode to electrolyte material engineering containing the knowledge on perspectives of both technology and material science. It provided an excellent starting point for the further research